Tonga national emergency medical team response to the 2022 Hunga Tonga-Hunga Ha’apai volcanic eruption and tsunami: the first deployment of the Tonga Emergency Medical Assistance Team (TEMAT) - Sifa, Siosifa; Fusi, Sela Ki Folau; Casey, Sean T; Poloniati, Penisimani; Tavo, Kaloafu; Setoya, Yutaro; 'Akauola, 'Ana (Western Pacific Surveillance and Response, 2023)
Problem: The undersea Hunga Tonga-Hunga Ha’apai volcano erupted on 15 January 2022, causing a tsunami that affected Tonga as well as other countries around the Pacific rim. Tonga’s international borders were closed at the time due to the coronavirus disease pandemic, but clinical surge support was needed to respond to this disaster.Context: Tonga’s Ministry of Health formed the Tonga Emergency Medical Assistance Team (TEMAT) in 2018 to provide clinical care and public health assistance during disasters, outbreaks and other health emergencies. TEMAT was activated for the first time in January 2022 to respond to medical and public health needs following the eruption and tsunami.Action: On 16 January 2022, a five-person TEMAT advance team was deployed to conduct initial damage assessments and provide casualty care. Subsequently, TEMAT rotations were deployed to provide clinical care and public health support across the Ha’apai island group for over 2 months.Outcome: TEMAT deployed to the islands most affected by the volcanic eruption and tsunami within 24 hours of the event, providing emergency clinical, psychosocial and public health services across four islands. TEMAT reported daily to the Ministry of Health and National Emergency Management Office, providing critical information for response decision-making. All TEMAT actions were documented, and an after-action review was conducted following the deployment.Discussion: TEMAT’s deployment in response to the 2022 volcanic eruption and tsunami highlighted the importance of national emergency medical teams that are prepared to respond to a range of emergency events.
Keywords: emergency medical team; volcanic eruption; tsunami; disasters; Tonga